The nodal violations in the time of epidemics and disasters - Sadhan, Madiha (Jordan Journal of Islamic Studies, 2023)
There is a new epidemic of “Corona” spread among people these days, as “Cofid-19”, and there is no disease or calamity in the soul except God has wisdom in it, including that the Almighty bring back His servants to Him by repentance, and shows them their weakness to trust in Him, and their inability to trust in Him, and invoke Him, What is observed is the presence of some contractual violations in light of these circumstances that worried many people, so it was obligatory for scientists and students of science to remind people of their religion, and to warn them of their violations, and this research came to contribute to spreading the correct science, And its title is: (Contractual violations in the time of epidemics), This research deals with the effect of neglecting reasons on faith. It sheds light on the judgment on therapy by unproven reasons. It also warns against neglecting the legitimate reasons and elaborates how going against the regulations and the rulers can play a key role in the spread of epidemics. The study also clarifies the reasons behind mistrusting Allah, like listening to hypocrites and inaccurate news.